THE FEATURES OF THE SEMANTICS OF NEGATION IN DIPLOMATIC TEXT - D. A. Golovanova (Vestnik MGIMO-Universiteta)
One of the crucial points of the article is an overview of the development of negation in linguistics which is considered to be one of the fundamental categories. The article explores the change in the paradigms of understanding negation in linguistics: from the structural approach to the cognitive one. The author presents such approaches as structuralism, the pragmatic conception and the cognitive approach. Besides, the peculiarities of functioning and the performance of the category are revealed in the article. Particular attention is paid to the cognitive approach as one of the main trends of modern linguistics. The focus on negation from the cognitive perspective allows to analyze both its functions in diplomatic text (some of them are represented in the article) and its dependence on external factors. Being a universal category, negation is reflected in all types of discourse, and the article concentrates on diplomatic discourse as the least studied one regarding its peculiarities from the linguistic perspective. On writing the particular features of negation from the perspective of cognitive linguistics, the author represents the analysis of oral diplomatic text and reveals the reciprocal conditionality of the semantic and formal aspects of negation. Also the dependence of its semantics on the opposition “my – foreigner’s” is presented.